How to implement Blue Ocean Strategy (BOS) in B2B sector - Čirjevskis, Andrejs; Homenko, Genadijs; Lačinova, Valērija (Business, Management and Economics Engineering, 2011)
The aim of research is to confirm the hypothesis that BOS is viable in the B2B sectors. The objects of research are two business entities: world’s leading suppliers of construction chemicals and manufacturer of purification equipment. Authors posed first research question is BOS a suitable within construction chemicals and purification equipment manufacturers’ industries? Second research question was about how to evaluate acceptability of new strategic choice on BOS? Third research question was how to diagnosis organisational hurdles on BOS implementation? Research has confirmed the hypothesis and suggested application of innovation value chain to diagnosing company’s ability to implement value innovation.